2008
DOI: 10.1007/s00421-008-0944-y
|View full text |Cite
|
Sign up to set email alerts
|

Influences of a dietary supplement in combination with an exercise and diet regimen on adipocytokines and adiposity in women who are overweight

Abstract: The influence of a proprietary blend of modified cellulose and cetylated fatty acids (Trisynextrade mark, Imagenetix, Inc., San Diego, CA 92127, USA) on adipocytokine and regional body composition responses to a weight loss program was examined. Twenty-two women (Supplement group (S) (n = 11): age = 36.8 +/- 7.2 years; weight = 87.1 +/- 6.2 kg; % body fat = 43.4 +/- 4.1; Placebo group (P) (n = 11): age = 38.3 +/- 6.8 years; weight = 86.9 +/- 4.7 kg; % body fat = 44.3 +/- 2.0) completed an 8-week placebo-contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…In 27 (51.9%) studies, evaluation of the intervention effect on adiponectin blood levels was the primary outcome, while in others, determination of adiponectin levels was a secondary outcome 21–23,26–29,31,36,38–40,43,46,47,53–55,60,62,65,68,69,71 . Most studies (90.4%) analyzed only the total adiponectin form, while the measurement of at least one of the adiponectin multimeric forms was performed in five studies 26–28,42,71 .…”
Section: Literature Search and Quality Of Studiesmentioning
confidence: 99%
See 3 more Smart Citations
“…In 27 (51.9%) studies, evaluation of the intervention effect on adiponectin blood levels was the primary outcome, while in others, determination of adiponectin levels was a secondary outcome 21–23,26–29,31,36,38–40,43,46,47,53–55,60,62,65,68,69,71 . Most studies (90.4%) analyzed only the total adiponectin form, while the measurement of at least one of the adiponectin multimeric forms was performed in five studies 26–28,42,71 .…”
Section: Literature Search and Quality Of Studiesmentioning
confidence: 99%
“…The number of participants ranged from 10 31 to 219 70 . Fifteen (28.8%) studies included only females, 20,23,24,26,29,31,32,45,49,51,55,63,65,66,70 and seven (13.5%) included only males 22,28,39,40,53,54,69 . Two studies did not report the gender of participants, 42,57 and other studies ( n = 28) included both female and male participants.…”
Section: Literature Search and Quality Of Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…While many studies have shown that serum leptin concentrations decrease following weight loss [14, 22-36], the relationship between serum adiponectin concentrations and weight loss is less clear, although some studies indicate that adiponectin concentrations increase following weight loss [24-26, 29, 36-42]. Similarly, the effect of exercise on serum adipokines is also unclear.…”
Section: Discussionmentioning
confidence: 99%